Gray Matter Differences Between Premature Pubertal Girls With and Without the Reactivation of the Hypothalamic—Pituitary-Gonadal Axis - Fu, Yuchuan; Zhang, Wenjing; Tao, Bo; Yang, Beisheng; Yang, Di; Xie, Xiaoling; Liu, Peining; Zhu, Yaxin; Zhou, Lu; Chen, Tao; Liu, Xiaozheng; Yan, Zhihan (Frontiers in Psychiatry, 2020)
The onset of puberty and related hormones exerts significant effects on brain morphometric and psychosocial development. The biological mechanisms underlying how the reactivation of the hypothalamic -pituitary -gonadal (HPG) axis and puberty-related hormonal maturation sculpts human brain architecture remain elusive. To address this question, 105 premature pubertal girls (age 8-11 years) without menstruation underwent brain structural scanning on a 3T MR system, and the luteinizing hormone releasing hormone (LHRH) stimulation test was used to identify the reactivation of the hypothalamic -pituitary -gonadal axis (HPG). Among the 105 girls, 63 had positive HPG axis reactivation (HPG+), while the others showed negative reaction (HPG-). Cortical thickness was calculated and compared between the two groups after adjusting for age. The brain regions showing inter-group differences were then extracted and correlated with the peak value of serum hormone after the LHRH stimulation test in entire sample. Compared to HPG- girls, HPG+ girls showed reduced cortical thickness mainly in the right precuneus, right inferior temporal gyrus, and right superior frontal gyrus, and increased cortical thickness primarily in the left superior parietal lobe and right inferior parietal lobe. Linear-regression analysis revealed negative correlations between the cortical thickness of the right inferior parietal lobe with the peak value of FSH, and between the right precuneus and LH and E2. These findings provide evidence supporting the notion that the reactivation of HPG axis and changes of hormones during the early phase of hormonal maturation would exert influences on the development of gray matter.